2015
DOI: 10.1055/s-0040-1703912
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid fossa and mid shaft circumference of the clavicle - anthropological study in North Karnataka population

Abstract: The rhomboid fossa of clavicle was studied globally by forensic experts and anthropologists to determine the age and sex. This study was done on samples of human clavicles from North Karnataka of South India to determine the sexual dimorphism which is of anthropological, forensic and clinical importance. In this study mid shaft circumference, morphology of rhomboid fossa of clavicle was analysed. The incidences of rhomboid fossa of depressed and elevated types are seen more in males and smooth and flat types a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…This was assumed to support the mechanical force of fossa formation. Similar to the Indians, this high incidence of Type 4 was found approximately in 67% [ 17 ]. In contrast to Greece and Indians, Type 4 fossa in Northeastern Thais was approximately 3.78% ( Table 1 ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…This was assumed to support the mechanical force of fossa formation. Similar to the Indians, this high incidence of Type 4 was found approximately in 67% [ 17 ]. In contrast to Greece and Indians, Type 4 fossa in Northeastern Thais was approximately 3.78% ( Table 1 ).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have reported only two types (depressed and smooth) of clavicular rhomboid fossa in many populations such as Greeks [ 13 ], Americans [ 15 ], Brazilians [ 16 ], North Karnataka [ 17 ], North Indians [ 21 ], and Greeks [ 22 ]. In our observations ( Figure 1 ), the types of rhomboid fossa were similar to that investigated in Indian clavicles which were classified into 4 types (smooth, flat, elevated, and depressed) [ 17 ]. It is possible that the lifestyles of these two populations are similar such as agricultural occupations in rural areas that might affect the rhomboid fossa development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a number of studies have reported that morphometric parameters of the clavicle vary between population affinities (Akhlaghi, Moradi, & Hajibeygi, ; Alcina, Rissech, Clavero, & Turbón, ; Ishwarkumar, Pillay, Haffajee, & Rennie, ; Králík, Urbanová, & Wagenknechtová, ; McCormick, Stewart, & Greene, ; Murphy, ; Patel, Shah, Merchant, Nirvan, & Shah, ; Spradley & Jantz, ). For example, previous studies have shown that the incidence of rhomboid fossae, a skeletal trait produced by the costoclavicular ligament which connects the first rib to the clavicle, may differ between the sexes and may be influenced by biological or population affinity (Bhat, Asif, Manjegowda, Radhakrishna, & Shivarama, ; Jit & Kaur, ; Kaewma, Sampannang, Tuamsuk, Kanpittaya, & Iamsaard, ; Paraskevas et al, ; Prado et al, ; Rogers, Flournoy, & McCormick, ).…”
Section: Introductionmentioning
confidence: 99%